2010
DOI: 10.2320/matertrans.m2009390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Braking Speeds on the Tribological Properties of Carbon/Carbon Composites

Abstract: This paper describes the tribological properties of carbon/carbon composites used as braking materials under various braking speeds, in which the materials with three kinds of microstructures were used: rough lamina (sample A), smooth lamina (sample B), and the mixture of rough lamina and smooth lamina (sample C), respectively. Friction tests were carried out through a laboratory dynamometer. Polarized optical microscopy (OM) and scanning electron microscopy (SEM) were used to characterize the microstructure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…and matrix microstructure (orientation of graphitic planes and fibre/matrix interfaces): in turn, these latter features control the material properties. [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17][18] In the present work, objective was to make two C f / C m composites, Type A and Type B through an economical route without employing costlier CVI process. These two composites had 2D fibre arrangements but different types and volumes of carbon fibre reinforcements.…”
Section: Step 3: Graphitisation Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…and matrix microstructure (orientation of graphitic planes and fibre/matrix interfaces): in turn, these latter features control the material properties. [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17][18] In the present work, objective was to make two C f / C m composites, Type A and Type B through an economical route without employing costlier CVI process. These two composites had 2D fibre arrangements but different types and volumes of carbon fibre reinforcements.…”
Section: Step 3: Graphitisation Treatmentmentioning
confidence: 99%
“…1,[8][9][10] The impregnation-pyrolysis cycle is repeated until the product has the desired density. Although the CVI process takes a relatively long time and is costlier, its economic disadvantage is offset by much better properties in the final product.…”
Section: Introductionmentioning
confidence: 99%
“…C/C composites are generally manufactured through chemical vapor deposition (CVD) technique with the impregnation of resin or pitch or the process combining both . These composites can also be manufactured by solid pyrolysis using thermosetting resins, or pitch route using liquid infiltration carbonization route .…”
Section: Introductionmentioning
confidence: 99%
“…C/C composites are generally manufactured through chemical vapor deposition (CVD) technique with the impregnation of resin or pitch or the process combining both. 10 These composites can also be manufactured by solid pyrolysis using thermosetting resins, or pitch route using liquid infiltration carbonization route. 9 The first step in the fabrication of C/C composites involves the fabrication of a three-dimensional-reinforced or multidimensional porous carbon fiber preforms with desired architecture or porous carbon-carbon skeleton with carbon fibers and a carbonaceous matrix followed by their densification.…”
Section: Introductionmentioning
confidence: 99%
“…and the surrounding environment. Several studies have been carried out and reported in the literature to study the effect of different parameters like properties of fibre reinforcement 11 , fibre architecture 12 , fibre orientation 13 , pressure during densification 9 , heat treatment temperature 14 , sliding velocity/braking speed and brake pressure [15][16] , energy absorbed by the brakes 7 , air/nitrogen atmosphere 17 and humidity 18 , on friction and wear of C/C aircraft brake discs. The type of carbon matrix is one of the important parameters that influences the friction and wear of C/C brakes.…”
mentioning
confidence: 99%